Reviewers’ views on the editorial review processes of the Canadian Medical Education Journal - Lotoski, Larisa; O’Brien, Jennifer; D’Eon, Marcel F (Canadian Medical Education Journal, 2025)
Background: Peer review is an integral part of the scientific process, ongoing efforts are needed to improve this process for both the reviewer and the scientific journal conducting peer review. This work describes the Canadian Medical Education Journal (CMEJ) peer reviewers’ experiences in accepting or declining invitations to review. Methods: We deployed questionnaires between December 2020 and May 2022. We calculated descriptive statistics for each response group (accepted or declined invitations). We analyzed open-ended comments using conventional content analysis. Results: CMEJ Reviewers described their experiences within three broad categories of factors: individual, contextual, and journal. Participants strongly agreed or agreed to review an article (n = 95) because the article was: within their area of expertise (84/95 = 88.4%); within a topic of interest (n = 83, 87.4%); an appropriate length (n = 79, 83.2%); relevant to their work and/or interests (n = 77, 81.1%); of sufficient quality (n = 75, 78.9%); educational (n = 72, 75.8%); and provided the opportunity to remain up-to-date on current research (n = 69, 72.6%). Participants’ (n = 17) most cited reason for declining their invitation to review for CMEJ was competing workloads (n = 14, 82.4%). Reviewers appreciated reviewer instructions, knowing the article’s outcome, and seeing what other reviewers had to say. Conclusion: This work describes the enablers and barriers of CMEJ reviewers and highlights the need to acknowledge peer reviewers' work, while challenging institutions and journals to support peer review activities.